Moral Aqidah Learning Using Video-Based Technology - Nicholas, Tsai; James, Grub; Robert, Kebede (Scientechno: Journal of Science and Technology, 2023)
There are lots of technologies that can be used in education. One of these technologies is video-based. Video is a visualization that can be used to facilitate the learning process, such as the Youtube application, where this application is beneficial for educators in developing video-based learning for moral theology learning media. With that in mind, this study aims to determine the benefits of video in learning moral theology. Learning moral theology often bored students because educators only use the lecture method without creativity to develop more effective and innovative learning. The type of method used in this research is quantitative by conducting surveys and interviews with teaching staff. The results of this study explain that video-based technology can help learn moral theology. This study concludes that educators can take advantage of videos for teaching moral principles based on evidence of student achievement and increased interest in learning, for this video-based technology can be used by any educator. The limitation of this research is that the researcher only researches moral theology subjects using video. The researcher hopes that future researchers will develop this strategy in other topics to get maximum results